O planejamento urbano do território rural: as “chácaras de recreio” e o jogo da ilegalidade no município de São Carlos (SP) - Rasera, Denise (Universidade Federal de São Carlos, 2024)
In the municipalities of the interior of the State of São Paulo, Brazil, many rural and peri-urban areas are occupied by "recreational farms", which are often characterized by their illegal nature. Initially sought primarily for leisure purposes, these areas are increasingly being absorbed by the "city," either through their incorporation as residential housing or the replication of residential developments in surrounding urban expansion areas. This study aims to analyze urban expansion through the lens of "recreational farm" developments, considering urban planning perspectives and the historical context of their establishment in a case study municipality. The discussion focuses on the advances and contradictions within federal and municipal land-use legislation related to "recreational farms." For this purpose, a case study was conducted in the municipality of São Carlos (SP), using various temporal frameworks according to the research objectives. The methods included bibliographic research, document analysis, semi-structured interviews, and the creation of visualization maps. The results highlight the persistence of illegal occupation processes in environmentally protected areas or areas with fragile soils, as well as the existence of contradictions in the regulation of rural territories.
Urban planning in rural areas: “recreational farms” and the game of illegality in the municipality of São Carlos (SP)
Keywords: “Chácaras de recreio”; Legislação; Planejamento urbano; Loteamentos ilegais; CIENCIAS EXATAS E DA TERRA